Evolusi Paradigma Respon Sosial terhadap Bencana : Analisis Literatur dari Pendekatan Reaktif ke Proaktif - Muh Nurikhsan; Syamsu A Kamaruddin; A. Octamaya Tenri Awaru (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research analyzes the evolution of social response paradigms to disasters from reactive to proactive approaches through a comprehensive literature review. The research method employs a qualitative approach with literature study techniques to identify driving factors of paradigm change and evaluate its implementation. The results show that paradigm transformation was triggered by several key factors: major disaster experiences such as the 2004 Aceh Tsunami, development of legal and institutional frameworks (Law No. 24 of 2007 and the establishment of BNPB), increased public awareness, and advancements in science and technology. Although the proactive approach has proven effective in reducing disaster impacts, its implementation still faces challenges including gaps between knowledge and practice, lack of integration with development planning, approaches that remain top-down, limited technology adoption, and disparities in regional fiscal capacity. This research contributes to the formulation of more adaptive and sustainable disaster management strategies through recommendations for strengthening participatory approaches, mainstreaming disaster risk reduction in development planning, and developing sustainable funding models for disaster mitigation and preparedness programs.